MiR-146a in myasthenia gravis thymus: from uncontrolled innate immunity to B cell-mediated autoimmunity: MiR-146a in MG thymus - Cavalcante, Paola; Tarasco, Maria Cristina; Iacomino, Nicola; Antozzi, Carlo; Mantegazza, Renato (RRNMF Neuromuscular Journal, 2023)
The thymus is the main site of autoimmunity development in myasthenia gravis (MG) associated with anti-acetylcholine receptor (AChR) autoantibodies, a prototypic autoimmune disease affecting neuromuscular junction. Most MG patients with early-onset disease presents follicular hyperplastic changes of the thymus, that are critically implicated in the initiation and perpetuation of the autoimmune response against the AChR. Uncontrolled activation of Toll-like receptor (TLR)-mediated innate immune responses, chronic inflammation and ectopic germinal center (GC) formation are key pathological features of hyperplastic thymus in MG, indicating that a close link between innate immunity and B cell-mediated autoimmunity underlies the intra-thymic pathogenesis of MG. MiR-146a, an “immune-miR” acting as key modulator of both innate and adaptive immunity, is a potent inhibitor of TLR signaling pathways, able to prevent and avoid an overstimulation of the inflammatory response by targeting the NF-κB signaling transducers IRAK1 and TRAF6. At the same time, miR-146a modulates the expression of c-REL, ICOS and ICOSL, which are crucial regulators of B cell function and GC response. Dysregulation of miR-146a expression is a common molecular event in several autoimmune disorders. Our recent findings revealed defective expression of miR-146a, associated with over-expression of its TLR- and B cell-related target genes, in follicular hyperplastic MG thymuses, indicating that loss of regulatory functions of this miRNA may significantly contribute to the immunopathological steps leading to MG. Of note, corticosteroids were found to increase the miR-146a expression levels, thus suggesting the miRNA capacity to mediate the effects of these drugs in inducing immunosuppression and autoimmunity control. In this review, we discuss the role of miR-146a as a molecular bridge between innate and adaptive immunity, and summarize the current knowledge on the miRNA contribution to the pathogenesis of MG. Based on our and literature data, we highlight the miR-146a potential as biomarker for therapeutic monitoring, as well as target of future advanced RNA-based therapies to modulate the immune system and counteract the autoimmune response in MG.